Monetary and Fiscal Policy Interactions: the Impact on the Term Structure of Interest Rates - Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
In this paper I consider a General Equilibrium framework to evaluate the role and the importance of the interactions between Monetary and Fiscal policies in the sense outlined by Leeper (1991) and the Fiscal Theory of the Price Level, in the determination of nominal and real term structure. The main results show that the term structure will depend not only upon monetary and technological factors - as in the traditional models - but also upon the fiscal policy reaction function parameters. This aspect is very useful in explaining the recent experience of some countries, like Italy, whose term structure shifted down after the fiscal retrenchement imposed by Fiscal Rules of Maastricht Treaty. In this paper the term structure is derived by using a very general approach, starting from implicit assumptions on the driving stochastic processes of the model, rather than imposing a specific structure right from the beginning. The results are consistent with the more recent results outlined by Fiscal Theory of the Price Level and by monetary models of the term structure.
Keywords: 330